ANALISIS KADAR KADMIUM DAN TIMBAL PADA AIR DI LIMA LOKASI SUNGAI TOTOK (Mulai aktivitas, 500 m dan mulai aktivitas, tengah, antara tengah dan muara dan muara) SULAWESI UTARA - Yorinda Buyang (Universitas Musamus, Merauke, Papua, 2013)
Thisstudy is aimed to know the content of the heavy metals, cadmium and lead in the Totok river water and to know is there cadmium and lead which was permissible limit. The samples was taken in five location. Cadmium and lead to heavy metals content is analyzed by using atomic absorption spectrometer fire place. Research results on Totok river water, consentration of heavy metal cadmium valued at 0.5690 to 1.1065 ppb and consentration heavy metal lead is 95.5000 to 190.6000 ppb. These result showed that the Totok river polluted by metal lead high enough